INSTRUCTIONS TO AUTHORS -2009 INDIAN JOURNAL OF PHARMACY PRACTICE (ijopp) - Rani R Hiremath, Dr. Shobha (Indian Journal of Pharmacy Practice)
Indian Journal of Pharmacy Practice (ijopp) is official journal of Association of Pharmaceutical Teachers of India (APTI). Indian Journal of Pharmacy Practice, a quarterly publication is devoted to publishing reviews and research articles in the area of Pharmacy Practice. Articles in the areas of clinical pharmacy, hospital pharmacy, community pharmacy, pharmaceutical care, pharmacovigilance, pharmacoeconomics, clinical research, clinical pharmacokinetics and other related issues can be sent for publication in ijopp.